1978
DOI: 10.1177/000348947808700318
|View full text |Cite
|
Sign up to set email alerts
|

Cricothyroid Muscle in Respiration

Abstract: Although the phonatory activity of cricothyroid muscle is well-known, its respiratory role often remains unrecognized. Recent data suggest this muscle plays a major role in the overall regulation of breathing by its control of expiratory resistance and flow. Cricothyroid contraction in expiration results in vocal elongation increasing glottic size. Such a mechanical effect reduces airway resistance and shortens expiratory duration. By such a mechanism, the rate of respiration may ultimately be modified using t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

1979
1979
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(12 citation statements)
references
References 10 publications
1
11
0
Order By: Relevance
“…This finding coincides with the experimental results of Hast (1967), Suzuki and Kirchner (1969), Suzuki et al (1970) and Horiuchi and Sasaki (1978) who worked on other types of mammals. They showed that the m. cricoarytenoideus posterior is active during inhalation but not during expiration.…”
Section: Discussionsupporting
confidence: 92%
“…This finding coincides with the experimental results of Hast (1967), Suzuki and Kirchner (1969), Suzuki et al (1970) and Horiuchi and Sasaki (1978) who worked on other types of mammals. They showed that the m. cricoarytenoideus posterior is active during inhalation but not during expiration.…”
Section: Discussionsupporting
confidence: 92%
“…The external branch of SLN supplies the cricothyroid muscle, which is the only tensor muscle of the vocal cords [37]. In addition to its contribution to phonation, the cricothyroid muscle plays a role in the overall regulation of breathing by its control of expiratory resistance and flow [53]. The nerve enters the cricothyroid muscle laterally on its deep surface.…”
Section: Innervation Of the Thyroid Glandmentioning
confidence: 99%
“…It is known that the human CT muscle is active during phonation 1-5 and respiration. [6][7][8][9][10] However, little is known about how its bellies work during both motor tasks. As neural control of a compartmentalized muscle is intimately bound up with muscle functions, 12,[15][16][17] separate nerve supply patterns of the CT bellies indicate that each of the bellies may activate independently and participate in specific upper airway motor tasks.…”
Section: Ct Bellies and Their Possible Functionsmentioning
confidence: 99%
“…Thus, CT muscle action is integral to lengthening, tensing, and adducting the vocal folds which are critical for its functions during phonation [1][2][3][4][5] and respiration. [6][7][8][9][10] The human CT is traditionally described as consisting of two bellies: rectus and oblique. However, a third belly has been revealed in the canine CT muscle by Zaretsky and Sanders.…”
Section: Introductionmentioning
confidence: 99%